The Relationship Between Teacher And Staff Motivation And Participative Decision Making On Job Satisfaction With Adversity Quotient As A Moderator In Indonesia - Sapulete, Vallyrina Trysia; Hidayat, Fachrudin (PT Keberlanjutan Strategis Indonesia, 2026)
Abstract: This study aims to examine the relationship between motivation and participatory decision-making and job satisfaction, with adversity quotient as a moderating variable, among teachers and staff in Indonesia. Using a quantitative correlational approach, data were collected from 101 respondents through an online questionnaire using a Likert scale, supplemented by semi-structured interviews. The variables analyzed included motivation and participatory decision-making as independent variables, job satisfaction as a dependent variable, and adversity quotient as a moderating variable. Data analysis was conducted using SPSS using correlation and multiple regression techniques, along with classical assumption tests to ensure the validity and reliability of the model. The results showed that motivation has a positive and significant relationship with job satisfaction, indicating that higher levels of motivation contribute to increased satisfaction among teachers and staff. Participatory decision-making also demonstrated a strong positive relationship with job satisfaction, highlighting the importance of involving employees in organizational decision-making processes. Furthermore, it was found that adversity quotient strengthened the relationship between participatory decision-making and job satisfaction, suggesting that individuals with greater resilience and ability to cope with challenges experience greater benefits from participation in decision-making. This study contributes to the literature by emphasizing the critical role of psychological resilience in enhancing the effectiveness of participatory management practices. These findings suggest that schools should foster motivation, encourage participatory decision-making environments, and develop resilience among teachers and staff to improve overall job satisfaction.